Self esteem and student participation in the activities of physical education and sport at high school education in Algeria Hechaichi Abdelouaheb & Yaqub Al Eid - Hechaichi Abdelouaheb; Yaqub Al Eid (Sultan Qaboos University, 2010)
The purpose of the present study was to investigate the difference between high school female and male students regarding participation in the lessons of physical education and self-esteem. The sample of this study comprised 305 students (136 males, 169 females). The Rosenberg self-esteem scale, and the Fox and Corbin physical self perception profile were administered to them. Results of the study revealed significant differences in self-esteem, particularly in physical self-esteem between students with high participation and students with low participation in physical education, as well as gender differences in self-esteem especially among students with low participation in the lesson of physical education. Results also demonstrated that the participation of female students in the lesson of physical education was not affected by the self esteem level.